E-226 Presentations and endovascular vs. surgical treatment selection of intracranial aneurysms: a real-world assessment from the NVQI-QOD cerebral aneurysm registry. (23rd July 2022) - Noorani, S; Bauknight, W; Abdalla, R; Tejada, J; Church, E; Sahlein, D; Howington, J; Ansari, S
Abstract : Introduction: ISAT and BRAT compared surgical and endovascular treatment modalities for ruptured aneurysms and provided limited information on presentations and demographics. However, these studies assessed predominantly small (<10mm) anterior circulation aneurysms and may not be generalized to all aneurysms. ISUIA analyzed effects of unruptured aneurysm size and location on rupture and treatment risks, but there is little data to support selection of endovascular versus surgical treatment. Furthermore, given the inconsistencies in aneurysm presentations, morphology, location, patient demographics, and rapidly improving endovascular and surgical technology, the real world practice of aneurysm management is highly variable and evolving. The NeuroVascular Quality Initiative-Quality Outcomes Database (NVQI-QOD) is a national registry of neurointerventional and cerebrovascular surgical procedures, that can be used to assess ruptured vs. unruptured aneurysm presentations and current trends in patient selection for endovascular vs. surgical treatment. Methods: We analyzed 4250 aneurysm cases from the 2015–2021 NVQI-QOD Cerebral Aneurysm Registry to compare differences in aneurysm presentations and current trends in treatment management across 4 subsets: Ruptured-Endovascular (N=1522), Ruptured-Surgical (N=208), Unruptured-Endovascular (N=2224), and Unruptured-Surgical (N=296). Descriptive analyses were performed across all four subsets followed by statistical differences in ordinal and categorical variables, including patient demographics/risk factors (age, sex, hypertension, smoking, etc.) and aneurysm characteristics (number, size, location, morphology), to assess for significant differences between unruptured and ruptured aneurysms as well as endovascular vs surgical treatment selection. Results: In comparison to ruptured aneurysms, patients that underwent treatment of unruptured aneurysms presented at an older age (59.2 vs 56.0; p<0.0001), with lower current smoking rates (30.2% vs 35.5%; p<0.01), higher proportion of multiple aneurysms (8.77% vs 5.14%; p<0.0001), and larger aneurysm size-width (5.98 mm vs 5.44 mm; p=0.0001). There was also a statistically significant difference in location between ruptured and unruptured cohorts (p<0.01): 34.7% vs. 46.0% in the ICA, 11.8% vs. 17.6% in the MCA, 33.3% vs. 20.1% in the ACA, and 20.1% vs. 16.2% in the posterior circulation (vertebral, basilar, PICA, SCA, PCA). Irrespective of rupture status, endovascular treated patients were older in age (58.4 vs 54.6 years, p<0.001) with larger aneurysm sizes (5.83 vs 5.09 mm width, p<0.001), but with less multiple aneurysm presentations (5.9% of endovascular vs 18.2% of surgically treated patients, p<0.001). Among unruptured aneurysms, ICA aneurysms comprised 50.1% endovascular vs. 15.6% surgical cases; MCA aneurysms comprised 13.0% endovascular vs. 52.2% of surgical cases. Among ruptured aneurysms, ICA aneurysms comprised 35.9% endovascular vs. 26.1% surgical cases while MCA aneurysms comprised 8.1% endovascular versus 38.6% surgical cases. Posterior circulation aneurysms comprised 22.1% of Endovascular-Ruptured, 17.7% of Endovascular-Unruptured vs. 5.8% of Surgical-Ruptured, 5.4% of the Surgical-Unruptured cohorts. Conclusions: Our findings demonstrate the current real-world practice, presentations and endovascular/surgical treatment selection of both unruptured and ruptured intracranial aneurysms. Compared to ruptured aneurysm treatment, unruptured aneurysms present at an older age with a lower current smoking rate, multiple aneurysms, larger sizes, and ICA/MCA (over ACA and posterior circulation) locations. Key determinants that favor endovascular over surgical treatment selection include older age, single aneurysm, larger size, and ICA or posterior circulation (over MCA) locations. Disclosures: S. Noorani: None. W. Bauknight: None. R. Abdalla: None. J. Tejada: None. E. Church: None. D. Sahlein: None. J. Howington: None. S. Ansari: None.